ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA (STUDI KASUS PADA PT. HSI) - Gutara, Mohamad Yudha; Rahma, Ika Nur (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The era of globalization has triggered global industrial development. The large number of competitors is a challenge and even a threat for companies to survive. Considering the large influence the quality of human resources has on achieving company goals, it is important for companies to provide special treatment to their employees. Human resource development is the key to realizing this goal. The aim of this research is to explain the situation accurately and systematically regarding the conditions of human resource development at PT. HSI. The research method used is a qualitative method with a qualitative descriptive design. The subject selection technique in this research was purposive sampling. The criteria for informants/subjects in this research are 1) Working at PT. HSI, (2) Have at least one year of experience working as a leader at PT. HSI 3) Have at least one year of experience working at PT. HSI. The results of this research show that human resources (employees) are company assets, which are the main support for organizational goals. Potential human resources need to be maintained by continuing to develop employee competencies and skills. Human resource development can be improved by holding various types of training related to employee skills and expertise in carrying out production processes in the field.